2018
DOI: 10.1007/s12011-018-1591-8
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Attenuates Staphylococcus aureus Mastitis in Mice by Inhibiting the Activation of the NALP3 Inflammasome and NF-κB/MAPK Pathway

Abstract: Mastitis is one of the most important diseases affecting the dairy industry in the world, and it also poses a great threat to human food safety. In this study, we explored whether selenium can inhibit the activation of the NALP3 inflammasome and NF-κB/ MAPK pathway to achieve anti-inflammatory effects. Sixty BALB/c female mice were randomly divided into three groups according to diets of different selenium concentrations (high, normal, and low). After 90 days, mice fed the same selenium concentration were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The infection not only affects the milk quality, but also poses a huge threat to food safety due to bacterial toxins and antibiotic residues ( 29 , 30 ). Selenium was widely applied in dietary supplements for its antioxidative and anti-inflammatory effects ( 24 , 31 ). In this study, the anti-inflammatory functions of OS were evaluated using a rat mastitis model induced by S. aureus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection not only affects the milk quality, but also poses a huge threat to food safety due to bacterial toxins and antibiotic residues ( 29 , 30 ). Selenium was widely applied in dietary supplements for its antioxidative and anti-inflammatory effects ( 24 , 31 ). In this study, the anti-inflammatory functions of OS were evaluated using a rat mastitis model induced by S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…Trizol reagent was used to extract total RNA from the mammary tissues (Vazyme Biotech Co., Ltd, China). The concentration and purity of RNA were measured using NanoDrop 2000 spectrophotometer (Thermo Scientific, USA) as described previously ( 24 ). The RNA samples of A260/280 ratio ranging from 1.90 to 2.0 were selected for cDNA synthesis using HiScript® QRT SuperMix (Vazyme Biotech Co., Ltd, China).…”
Section: Methodsmentioning
confidence: 99%
“…Selenium (Se) is an essential micronutrient that is necessary for proper antioxidant defense, reproduction, cancer prevention, immunity and health [ 121 ]. Several studies have demonstrated, that selenium by inhibition of the NLRP3 inflammasome activity attenuates Staphylococcus aureus mastitis and has an anti-inflammatory property in the mammary gland [ 122 , 123 ]. In a mouse model of Staphylococcus aureus -induced mastitis selenium administration in the diet was found to suppress NALP3 inflammasome expression and inhibit the maturation of caspase-1 and IL-1β in mammary tissue.…”
Section: Substances That Can Inhibit Inflammasome Activitymentioning
confidence: 99%
“…In a mouse model of Staphylococcus aureus -induced mastitis selenium administration in the diet was found to suppress NALP3 inflammasome expression and inhibit the maturation of caspase-1 and IL-1β in mammary tissue. Selenium decreases the production of IL-1β by inhibiting activation of the NF-κB/p65 signaling pathway induced by Staphylococcus aureus, and downregulation of the NALP3 inflammasome and ASC expression participates in inflammation reduction [ 122 , 123 ]…”
Section: Substances That Can Inhibit Inflammasome Activitymentioning
confidence: 99%
“…Moreover, the NLRP3 in ammasome was proven to be activated by S. aureus in monocytes/macrophages [17]. The activation of the NLRP3 in ammasome promotes the maturation of caspase-1, which then processes pro-IL-1β into IL-1β [18,19]. On the other hand, NF-κB and MAPK are involved in the activation of NLRP3 in ammasome, furthermore activated NF-κB and MAPK can recruit a series of cytokines and chemokines, including TNF-α and IL-1α [20].…”
Section: Introductionmentioning
confidence: 99%